Analysis of Financial Reports in Assessing Financial Performance using the Common Size Method at PT Telkom Indonesia (Persero) Tbk. - Raden Faiz Mustofa; Susy Hambani; Maria Magdalena (Journal of Finance and Business Digital, 2023)
The aim of this research is to analyze and evaluate the financial condition of PT. Telkom Indonesia Tbk. From a financial perspective, what are the conditions for the period 2017 to 2021. The descriptive method with a comparative approach is used in this research to obtain and obtain answers to the problems currently being researched by describing the company's financial performance. in the 2017 – 2021 reporting year using the Common Size technique. The results of the research show that financial performance according to the common size is quite good because the average composition of the amount of debt is a smaller percentage compared to capital in the company's operational fund allocation and in terms of PT's profit and loss. Telkom Indonesia Tbk. from 2017 to 2021 it continued to generate profits every year, the decline in 2018 was due to an increase in expenses.